The Effect of Transformational Leadership On Innovative Work Behavior Moderated by Psychological Empowerment Variable On Employees Of Hv Tang Aia Tourist Object: Pengaruh Kepemimpinan Transformasional terhadap Innovative Work Behavior melalui Psychological Empowerment pada Karyawan Objek Wisata HV Tang Aia - Prima Dimas Putra; Mega Asri Zona (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research for influence transformational leadership on Innovative Work Behavior with Psychological Empowerment as a moderating. The research uses the Social Exchange Theory to explore these relationshi[. The object of this research is HV Tang Aia tourist attraction. This research have 45 responden. The sampling technique in this study used total sampling. This research used primary data from questionnaires via google form, with measurements 5-point Likert scale. The results showed that transformational leadership has positive and signifikan affects innovative work behavior. Psychological empowerment can moderate the relationship between transformational leadership and innovative work behavior in employees.